Pertentangan Rasionalitas Instrumental dan Nilai di Era Covid-19 - Febri Tory; Afrizal Afrizal; Bob Alfiandi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
This article discusses the conflict between instrumental rationality and value rationality. The purpose of the article is to re-examine what the differences are between the two and what are the causes of the conflict. The finding shows that contradictory actions would not have occurred if there were no people who had a tendency to place more importance on the dominant rules and were accompanied by the awareness to implement them. The only way to stop it is to